The Herders - Annie Wilson (Symphony in the Flint Hills, 2015)
This is a poem written by Annie Wilson capturing a glimpse of herding cattle and the realization of an ancient connection to peoples of the past.
Keywords: poem; Annie Wilson; buffalo; ranch; herders; Maasai; Mongols; beauty; beasts; steppe